Pengaruh Pemberian Madu dalam Meningkatkan Status Gizi pada Anak Usia Toddler - Anita Wulan Ningrum; Surati Ningsih (Indonesian Journal on Medical Science, 2022)
Health conditions in infants could be affected by appetite, sleep quality, weight, and haemoglobin. In the Sukoharjo District Hamlet, there were approximately 6 of the 20 toddler children with nutritional status problems or children with the Red Bottom Line (BGM). One of the causes of malnutrition in children was a decrease in appetite. This study was to describe the management of honey to improve nutritional status in toddler age children. The type of research used was descriptive qualitative with a case study research approach. The data collection technique was taken by purposive sampling using inclusion criteria aged 1-3 years and toddlers with BB below BB ideal calculated by (2n+8). Child assessment data had difficulty eating, difficulty eating vegetables and fruit. Physical examination: non-luminous hair, dry lip mucosa, sunken eyelids, skin elastic turgor, no folds under the skin. BB measurement results below BB are ideal. Nursing diagnosis: imbalance of nutrients less than the body's needs b.d lack of food intake, the action taken is giving honey. The results of this study that after giving honey for 2 weeks there was an increase in appetite and an increase in BB in children (60%). There is an effect of giving honey with an increase in nutritional status in toddler age children.